2006
DOI: 10.1152/ajpendo.00530.2005
|View full text |Cite
|
Sign up to set email alerts
|

Increase in S6K1 phosphorylation in human skeletal muscle following resistance exercise occurs mainly in type II muscle fibers

Abstract: Increase in S6K1 phosphorylation in human skeletal muscle following resistance exercise occurs mainly in type II muscle fibers. Am J Physiol Endocrinol Metab 290: E1245-E1252, 2006. First published January 24, 2006 doi:10.1152/ajpendo.00530.2005.-To investigate the in vivo effects of resistance exercise on translational control in human skeletal muscle, we determined the phosphorylation of AMP-activated kinase (AMPK), eukaryotic initiation factor 4E-binding protein (4E-BP1), p70/p85-S6 protein kinase (S6K1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
126
5
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 161 publications
(157 citation statements)
references
References 41 publications
13
126
5
6
Order By: Relevance
“…Previous studies showed elevated 4E-BP1 phosphorylation after resistance exercise (4,38). However, changes in phosphorylation of 4E-BP1 and p70S6K in response to a bout of exercise do not necessarily correspond, and some previous studies have failed to find elevated phosphorylation of 4E-BP1 (9,10,23,29). We also did not detect an elevated rate of 4E-BP1 phosphorylation 24 h after exercise throughout the training and detraining periods, suggesting differential regulation of 4E-BP1 and p70S6K.…”
Section: Discussioncontrasting
confidence: 74%
“…Previous studies showed elevated 4E-BP1 phosphorylation after resistance exercise (4,38). However, changes in phosphorylation of 4E-BP1 and p70S6K in response to a bout of exercise do not necessarily correspond, and some previous studies have failed to find elevated phosphorylation of 4E-BP1 (9,10,23,29). We also did not detect an elevated rate of 4E-BP1 phosphorylation 24 h after exercise throughout the training and detraining periods, suggesting differential regulation of 4E-BP1 and p70S6K.…”
Section: Discussioncontrasting
confidence: 74%
“…A single bout of resistance exercise can increase AMPK Thr 172 phosphorylation (36) and AMPK ␣2 activity (37), but using similar resistance exercise to that used in the latter studies (36,37), AS160 phosphorylation was decreased in the present study. Although a significant increase in AMPK phosphorylation and ␣2-activity with exercise was not detected in the present study, ACC Ser 79 phosphorylation, an in vivo measure of AMPK activity, increased more than threefold.…”
Section: Discussionmentioning
confidence: 48%
“…Indeed, both resistance-type and endurance-type exercise increase AMPK activity (Fig. 2) (13,19,32,45) and decrease 4EBP1 phosphorylation ( Fig. 1) (11, 13, 19), and resistance-exercise may actually decrease PKB activity (11) in skeletal muscle of humans.…”
Section: Discussionmentioning
confidence: 99%